2015
DOI: 10.1128/mcb.00202-15
|View full text |Cite
|
Sign up to set email alerts
|

SRSF2 Is Essential for Hematopoiesis, and Its Myelodysplastic Syndrome-Related Mutations Dysregulate Alternative Pre-mRNA Splicing

Abstract: dMyelodysplastic syndromes (MDS) are a group of neoplasms characterized by ineffective myeloid hematopoiesis and various risks for leukemia. SRSF2, a member of the serine/arginine-rich (SR) family of splicing factors, is one of the mutation targets associated with poor survival in patients suffering from myelodysplastic syndromes. Here we report the biological function of SRSF2 in hematopoiesis by using conditional knockout mouse models. Ablation of SRSF2 in the hematopoietic lineage caused embryonic lethality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 50 publications
4
71
1
1
Order By: Relevance
“…Down-regulation of SRSF2 substantially led to cell cycle arrest and destabilization of the genome [107]. Recent reports documented that imbalanced expression of SRSF2 resulted in the reduced growth and imbalanced apoptosis of hematopoietic cells, especially bone marrow cells [108]. Deep RNA-seq results indicated that SRSF2 depletion mediated the aberrant splicing of hematopoiesis-related genes, including MEIS1 , UPF38 , PRKAA1 , RBM23 , PDK1 , PDE4DIP , MLL , and RNF34 , which are closely related to the homeostasis of myeloid progenitors [108].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Down-regulation of SRSF2 substantially led to cell cycle arrest and destabilization of the genome [107]. Recent reports documented that imbalanced expression of SRSF2 resulted in the reduced growth and imbalanced apoptosis of hematopoietic cells, especially bone marrow cells [108]. Deep RNA-seq results indicated that SRSF2 depletion mediated the aberrant splicing of hematopoiesis-related genes, including MEIS1 , UPF38 , PRKAA1 , RBM23 , PDK1 , PDE4DIP , MLL , and RNF34 , which are closely related to the homeostasis of myeloid progenitors [108].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Indeed, each major splicing factor mutation has been demonstrated to alter a large number of splicing events in cellular and animal models (Kim et al, 2015; Komeno et al, 2015; Kon et al, 2017; Obeng et al, 2016; Shirai et al, 2015; Wang et al, 2016). In particular, disease development has been functionally linked to the inclusion of a “toxic” exon in the Ezh2 gene in Srsf2 (P95H) knockin mice (Kim et al, 2015) and a polyadenylation switch event in the autophagy gene Atg7 caused by U2af1 (S34F) overexpression on a murine pro-B cell model (Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, mice with a heterozygous Srsf2P95H mutant develop a cytopenia by myelodysplasia whereas a homozygous Srsf2 knockout when induced in adults leads to cytopenia due to a decrease in hematopoietic progenitors associated with increased apoptosis mimicking a bone marrow aplasia. 96 Particularly, it has been shown that the Srsf2 P95H mutation in mice can lead to a missplicing and nonsense-mediated decay of Ezh2. 97 Knowing that SRSF2 mutations are enriched in leukemic transformation of MPNs (19% of the cases), this further establishes that EZH2 and the PRC2 complex are important factors in the development of MF and progression toward leukemia.…”
mentioning
confidence: 99%